2005
DOI: 10.1074/jbc.m407856200
|View full text |Cite
|
Sign up to set email alerts
|

Protein NPM3 Interacts with the Multifunctional Nucleolar Protein B23/Nucleophosmin and Inhibits Ribosome Biogenesis

Abstract: Protein B23/nucleophosmin is a multifunctional protein that plays roles in ribosome biogenesis, control of centrosome duplication, and regulation of p53 expression. A yeast two-hybrid screen was performed in a search for interaction partners of B23. The complementary DNA for a highly acidic protein, nucleoplasmin 3 (NPM3), was found in multiple positive clones. Protein NPM3 and its interaction with B23 were further characterized. Endogenous B23 was able to be co-immunoprecipitated with NPM3, and this complex w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
84
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 33 publications
8
84
0
Order By: Relevance
“…The oligomerization of NPM1 is essential for at least some of its functions in vivo, likely through allowing simultaneous and closely juxtaposed binding of multiple targets or of multi-subunit complexes (Thyagarajan et al 1998;Xia et al 2013). Interestingly, NPM3 has not been reported to form homopentameric rings and is unable to act as a histone chaperone in its own right; instead, it assembles into hetero-oligomers with NPM1, in doing so promoting the histone chaperone activity of NPM1 while repressing its RNA-binding and ribosome biogenesis activities (Finn et al 2012;Huang et al 2005;Okuwaki et al 2012). D r a f t 8 Consistent with its identification as a nucleolar phosphoprotein, NPM1 undergoes extensive posttranslational modifications including phosphorylation, ubiquitination and SUMOylation, arginine methylation, lysine acetylation and others (Colombo et al 2011), demonstrating it to be a highly regulated protein in vivo.…”
Section: Nucleophosmin and Nucleolin: Two Multifunctional Nucleolar Pmentioning
confidence: 99%
“…The oligomerization of NPM1 is essential for at least some of its functions in vivo, likely through allowing simultaneous and closely juxtaposed binding of multiple targets or of multi-subunit complexes (Thyagarajan et al 1998;Xia et al 2013). Interestingly, NPM3 has not been reported to form homopentameric rings and is unable to act as a histone chaperone in its own right; instead, it assembles into hetero-oligomers with NPM1, in doing so promoting the histone chaperone activity of NPM1 while repressing its RNA-binding and ribosome biogenesis activities (Finn et al 2012;Huang et al 2005;Okuwaki et al 2012). D r a f t 8 Consistent with its identification as a nucleolar phosphoprotein, NPM1 undergoes extensive posttranslational modifications including phosphorylation, ubiquitination and SUMOylation, arginine methylation, lysine acetylation and others (Colombo et al 2011), demonstrating it to be a highly regulated protein in vivo.…”
Section: Nucleophosmin and Nucleolin: Two Multifunctional Nucleolar Pmentioning
confidence: 99%
“…Overexpression and tumorigenic activation of the Smoothened (SMO) protooncogene mediates c-myc overexpression, suggesting that SMO may also be a prognostic factor in HCC tumorigenesis (Sicklick et al, 2006). Nucleophosmin (NPM) is a major nucleolar phosphoprotein implicated in multiple cellular functions, including ribosomal protein assembly and transport (Verheggen et al, 2000;Huang et al, 2005), centrosome duplication (Okuda et al, 2000;Okuda, 2002;Grisendi et al, 2005), molecular chaperone activity in preventing protein aggregation (Hingorani et al, 2000;Szebeni et al, 2003), and regulating the activity of the tumour suppressors p53 (Colombo et al, 2002;Li et al, 2004;Maiguel et al, 2004) and p14 ARF (Itahana et al, 2003;Bertwistle et al, 2004;Brady et al, 2004). Earlier studies have shown that the level of NPM is markedly and promptly increased in association with cell commitment to mitogenesis (Feuerstein and Mond, 1987;Feuerstein et al, 1988).…”
mentioning
confidence: 99%
“…Proteins of the NPM3 type include a group of molecular chaperones that are ubiquitously expressed in many tissues, showing the highest levels in pancreas and testis and the lowest in lung, in the case of humans (Shackleford et al 2001). Like NPM1, NPM3 is mainly localized to the nucleolus in interphase cells and active rRNA transcription appears to be required for this localization (Huang et al 2005). NPM3 forms a complex with NPM1 and has been implicated in regulation of NPM1 function in ribosome biogenesis (Huang et al 2005).…”
mentioning
confidence: 99%